Comparative study of the antibacterial action of natural and commercial oils of Rosmarinus officinalis L - Mazouz , lakhdar (Algerian Journal of Biosciences, 2022)
The article tries to shed light on the antibacterial power of rosemary oils to see if there is a possibility of making drugs but also to compare this power with that existing in commercial oils of rosemary and to check if these formulas really contain oils rosemary. This study consisted of the extraction of the essential oil from the studied plant followed by preliminary phytochemical tests and then by TLC analyzes to determine exactly the different compounds that characterize the species and then by the antibacterial study on the plants diluted essential oils (synthesized and commercial). Phytochemical tests have shown that essential oils contain many chemicals and active ingredients that give rosemary a wide range of indications : The TLC of the raw extract shows stains, indicating the presence of flavone, hydroxyflavone, Dihydroxyflavone, flavanones, methoxyflavones and flavonols ; they are compounds of paramount importance in the therapeutic effects enjoyed by rosemary. The bacteriological study on essential oils (extract and commercial) by the process represented on the concentrated disk of essential oils shows good antibacterial activity on the fixed stem. Essential oils extracted from rosemary from Algeria will be of some economic interest in the Algerian pharmaceutical industry. The negative test for commercial rosemary essential oil compared to the positive tests of our extract can tell us more about the counterfeit that characterizes this area. The study confirms the interest we must bring to this plant, not only for its characteristics in the perfume industry, but especially for its undisputed medical virtues.